Analysis of the influence of quality, price, brand, facilities and models on the decision to purchase a Blackberry cellphone (case study on STIE IBS students) - Adhi Mulya Puspo (Indonesia Auditing Research Journal, 2021)
The objectives of the research are to know the effects of quality, price, brand, facilities or feature, and models of BlackBerry mobile phone towards the consumers' decision making in purchasing BlackBerry mobile phone, and to identify what factors have a dominant effect on the consumers' decision making of purchasing BlackBerry mobile phone in STIE IBS. After an examination of 145 respondents by multiple regression analysis, the study found that : (1) the significance value of 0.000 or 0.000 ≤ 0.05. This indicates that there are significant effects of of quality, price, brand, facilities, and models of BlackBerry mobile phone towards the consumers' decision making in purchasing BlackBerry mobile phone in STIE IBS. Thus, the fourth hypothesis could not be ignored. (2) Among the independent variables that were examined, facilities or feature has a dominant and significant effect on consumers' decision making in purchasing BlackBerry mobile phone. (3) Viewed from the collective test of factors on consumers' decision making in purchasing BlackBerry mobile phone, then: (a) Obtained a strong correlation between X1, X2, X3, X4, X5 due to R> 0.5 is 26.3% (adjusted R square) influence on purchasing decisions, while the rest are caused by other factors that is not examined. (b) On the variable facilities is seen that p value of 0.001 or 0.000 ≤ 0.05, so that it can be said H0 could not be rejected, which means the facilities variable significantly influence the consumers' decision making in purchasing BlackBerry mobile phone,The findings show that facilites or feature has a very significant effect of decision making in purchasing BlackBerry mobile phone.